Novel C-2 Aromatic Heterocycle-Substituted Triterpenoids Inhibit Hedgehog Signaling in GLI1 Overexpression Cancer Cells - Frydrych, Ivo; Choma, Barbora; Slavíková, Lucie; Pokorný, Jan; Jakubcová, Nikola; Ludha, Sandra; Gurská, Soňa; Řehulka, Jiří; Lišková, Barbora; Džubák, Petr; Hajdúch, Marián; Urban, Milan (ACS omega, 2025)
The hedgehog signaling pathway plays an important role in vertebrate embryonic development, tissue homeostasis, and tumorigenesis. Constitutive activation of Hh signaling in various human tumors leads to GLI-mediated transcription and tumor progression. Based on the preliminary screening of a large library of known triterpenes that exhibited interesting Hh inhibitory activity, we designed and synthesized a new series of triterpenoid analogues containing aromatic heterocyclic substituents at position C-2 to enhance their interference with Hh signaling. In this study, we evaluated the effect of 15 synthesized triterpenoids on cell proliferation and Hh pathway activity in relevant cancer cell lines. Among these compounds, two derivatives, 11a and 11b, both featuring a furan ring at position C-2, demonstrated potent inhibitory effects on proliferation and induced cell death in nonsmall cell lung cancer (NSCLC) and prostate cancer cell lines exhibiting hyper-activated Hh signaling. Moreover, these compounds significantly reduced GLI-mediated transcription in cell-based reporter assays. Detailed immunoblot analyses revealed that compounds 11a and 11b decreased the expression of endogenous GLI1 protein and its target genes associated with tumor progression and proliferation, such as Cyclin D1, N-Myc, and Bcl-2, in A549 and DU-145 cancer cells. These findings suggest that the antiproliferative effects of 11a and 11b are mediated through inhibition of the Hh signaling pathway and are promising candidates for the development of new anticancer therapies targeting Hh-dependent tumors.